On the subject of cloud cryptography - O. O. Chudak (Academy of Cognitive and Natural Sciences, 2013)
At the present time in Ukraine in connection with joining the world information space the latest achievements of computer and telecommunication technologies are being introduced at a rapid pace. Telecommunication systems are being actively introduced in the financial, industrial, commercial and social spheres. In this connection, the interest of a wide range of users in the problems of information protection has sharply increased. To transmit a large amount of information through a network requires a significant amount of bandwidth consumption. And when it is also necessary to encrypt each message, it consumes both additional bandwidth and overloads the network (the load on the router). Therefore, some providers to eliminate these disadvantages use cloud technology - a large or significant number of computers combined into a single system and designed to perform the selected type of tasks. This allows several times faster work. Calculations that require significant computing power will be handled by cloud technology, thereby relieving the router of additional calculations. Providers of these technologies, especially at strategic locations, are located primarily in the telecommunications room (server room). Cloud technology has its own drawbacks: the compute centers are individual workstations, united by a local network, so they are demanding on resources. But this disadvantage still does not prevent the use of cloud technology today.